Social and entrepreneurial values profiles - Martinez, Naylia de Brito (2014)
The person of the entrepreneur has intrigued academics for years. Consequently, numerous approaches have been applied to understand who the entrepreneur is, his personality and behaviors. The main schools debating about this topic are the psychological traits school and the processes or behaviors school. However, the academy still lacks an agreed upon definition of the individual triggering the entrepreneurial phenomenon. Consequently, in an attempt to clarify this issue, this research suggests a new approach for understanding the individual of the entrepreneur on the basis of Schwartz’s personal values. Hence the objective of this study is to understand the values profile of social and commercial entrepreneurs in order to determine their similarities which guide their common entrepreneurial behavior and their differences which generate their different entrepreneurial focus, one aiming at social and the other at private wealth. For this purpose, the shorter version of Schwartz’s Profile Values Questionnaire was administered to a sample of 44 social entrepreneurs and 71 commercial entrepreneurs. The first proposition of this study was that social and commercial entrepreneurs possess a value profile. The second was that this value profile was determined by the anxiety organizing principle with preponderance of the anxiety-free over the anxiety-based values. The third proposition was that commercial as well as social entrepreneurs attribute highest importance for the self-direction value. The fourth proposition was that social entrepreneurs give higher importance than commercial entrepreneurs for benevolence and universalism values because these values presume appreciation of others, preservation and enhancement of the welfare of 'in group' people as well as of any living being in general. The results of descriptive analyses and hypotheses testing point to the validation of all propositions except the last one. Nevertheless, although not statistically confirming the last proposition, a slight tendency of social entrepreneurs giving higher importance than commercial entrepreneurs for the selftranscendence values was identified. Consequently, other studies with larger and randomized samples should be conducted to better clarify this topic.